2010
DOI: 10.1007/s00417-010-1311-3
|View full text |Cite
|
Sign up to set email alerts
|

Early trabeculectomy bleb walls on anterior-segment optical coherence tomography

Abstract: Bleb wall reflectivity on AS-OCT 2 weeks after surgery may predict bleb function at 6 months, whereas IOP of developing blebs may not.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

6
53
2
2

Year Published

2011
2011
2020
2020

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 53 publications
(63 citation statements)
references
References 28 publications
(76 reference statements)
6
53
2
2
Order By: Relevance
“…Also, low intrableb reflectivity, episcleral fluid, and microcysts were identified in the images of the mature bleb and shown to be related with bleb function and IOP [16,[18][19][20]. Many reports support the notion that AS-OCT is useful in identifying intrableb morphology, and intrableb morphology was shown to be an important aspect in predicting bleb function [21].…”
Section: Discussionmentioning
confidence: 90%
See 1 more Smart Citation
“…Also, low intrableb reflectivity, episcleral fluid, and microcysts were identified in the images of the mature bleb and shown to be related with bleb function and IOP [16,[18][19][20]. Many reports support the notion that AS-OCT is useful in identifying intrableb morphology, and intrableb morphology was shown to be an important aspect in predicting bleb function [21].…”
Section: Discussionmentioning
confidence: 90%
“…Some internal features of the filtering bleb, such as formation of a cavernous fluidfilled space and intrableb reflectivity, have been characterized by ultrasound biomicroscopy (UBM) or anterior segment optical coherence tomography (AS-OCT), and these intrableb features are thought to be related to bleb function [9][10][11]. However, visualization of the internal morphologic changes of trabeculectomy blebs 12 months after ocular compression surgery has not been performed prospectively.…”
Section: Introductionmentioning
confidence: 97%
“…This technique is therefore very useful for the follow-up of glaucoma surgery, offering numerous criteria for evaluating bleb functioning, like length and height of the internal fluid-filled cavity, maximum and minimum bleb wall thickness, total bleb height, volumes of the internal fluid-filled cavity and hyporeflective area, and number of microcysts [53,54]. Nakano et al [55] even found that heterogeneity of bleb walls 2 weeks after surgery might predict the outcome of trabeculectomy at 6 months. …”
Section: Postoperative Evaluation Of the Blebmentioning
confidence: 97%
“…Yet, it also depends highly on the persistence of filtration efficiency at the bleb site. Therefore, postoperative observation and care of developing filtering bleb in clinical practice is an important tool in reaching the target pressure after filtration surgery in higher percentage of the patients [1].Bleb function is believed to depend on the degree of bleb fibrosis and obstruction of intrascleral aqueous humor flow [3]. Bleb appearance has been assessed using slit-lamp bio microscopy, gonioscopy, Ultrasound Bio Microscopy (UBM) and Optical Coherence Tomography (OCT).…”
mentioning
confidence: 99%
“…Bleb function is believed to depend on the degree of bleb fibrosis and obstruction of intrascleral aqueous humor flow [3]. Bleb appearance has been assessed using slit-lamp bio microscopy, gonioscopy, Ultrasound Bio Microscopy (UBM) and Optical Coherence Tomography (OCT).…”
mentioning
confidence: 99%